Pengaruh Infrastruktur dan Inovasi Hybrid Learning terhadap Kepuasan Mahasiswa Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Islam Bandung Angkatan 2020-2021 - M Dziqri Nur Rohiim; Aceng Komarudin Mutaqin (Bandung Conference Series: Statistics, 2023)
Abstract. The COVID-19 pandemic has an impact on all aspects of the world, including education in Indonesia. The Indonesian government together with the Ministry of Education and Culture then decides to implement a limited Face-to-Face Learning, namely Hybrid Learning. This makes University of Islam Bandung carry out Limited Face-to-Face Learnig for the even semester of the 2021/2022 academic year, the learning applied is hybrid, online, and offline. This certainly affects the satisfaction of students who are taking Hybrid Learning for the first time. Therefore, the researcher wants to examine the “Effect of Hybrid Learning Infrastructure and Innovation on Student Satisfaction of the Faculity of Mathematics and Science University of Islam Bandung Class of 2020-2021”. The population of this research is FMIPA student class 2020-2021 with a sample of 100 students. The analysis technique in this study is Multiple Linear Regression Analysis by testing several classical intruments and assumptions. Based on the results of the study, it can be concluded that infrastructure has no significant effect on satisfaction, innovation does have a significant effect on satisfaction. Obtained a value of 14,1% diversity of satisfaction can be explained by infrastructure and innovation. Meanwhile (100% - 14,1% = 86,9%) the rest is explained by other reasons outside the model. Abstrak. Pandemi COVID-19 berdampak terhadap segala aspek di dunia, termasuk pada pendidikan di Indonesia. Pemerintah Indonesia bersama dengan Kementrian Pendidikan dan Kebudayaan kemudian memutuskan untuk menerapkan PTM terbatas, yaitu Hybrid Learning. Hal itu membuat Unversitas Islam Bandung melaksanakan Pembelajaran Tatap Muka Terbatas untuk semester genap tahun ajaran 2021/2022, pembelajaran yang diterapkan yaitu hybrid, daring, dan luring. Hal ini tentunya berpengaruh terhadap kepuasan mahasiswa yang baru pertama kali mengikuti Hybrid Learning. Maka dari itu, peneliti ingin meneliti mengenai “Pengaruh Infrastruktur dan Inovasi Hybrid Learning terhadap Kepuasan Mahasiswa Fakultas MIPA Unisba Angkatan 2020-2021”. Populasi penelitian ini adalah mahasiswa FMIPA angkatan 2020-2021 dengan sampel sebanyak 97 mahasiswa. Teknik analisis dalam penelitian ini adalah Analisis Regresi Linear Berganda dengan menguji beberapa uji Instrumen dan Asumsi Klasik. Berdasarkan hasil penelitian, dapat disimpulkan bahwa infrastruktur tidak berpengaruh secara signifikan terhadap kepuasan, inovasi benar-benar berpengaruh secara signifikan terhadap Kepuasan. Didapat nilai 14,1% keragaman kepuasan dapat dijelaskan oleh infrastruktur dan inovasi. Sedangkan (100% - 14,1% = 86,9%) sisanya dijelaskan oleh sebab-sebab lain di luar model.